DESIGN OF BOGOR CITY DOMESTIC WASTEWATER TREATMENT PLANT - Rizki Izzaturrahman, Aristo
The increase in population density in Bogor City has the potential to adversely affect the sanitation conditions of the community's wastewater, leading to the risk of diseases due to environmental pollution. In this context, centralized wastewater treatment is considered a solution. This study designs a City-Scale Domestic Wastewater Treatment Plant (IPALD) with appropriate technology. The methodology involves problem identification, data determination, data processing, calculation of treatment unit dimensions, and determination of facility requirements. Wastewater quality data indicate values that do not meet standards, except for pH. Therefore, a treatment unit configuration is necessary to remove pollutants such as suspended solids, organic matter, nutrients, and pathogenic bacteria. Determining treatment units involves comparing aspects such as land use, operational ease, noise, odor, construction costs, and operational costs. The selected technologies and configurations include mechanical coarse screen channels, horizontal grit chambers, equalization tanks, primary clarifiers, Moving Bed Biofilm Reactor (MBBR), secondary clarifiers, and chlorination tanks. The sludge treatment configuration includes gravity thickeners, anaerobic digesters, and belt filter presses. The total Capital Expenditure (CAPEX) for Phases 1 and 2 is Rp329,404,480,000.00, with annual Operational Expenditure (OPEX) of Rp10,499,786,000.00 for Phase 1 and Rp16,711,588,000.00 for Phase 2. Economic analysis using NPV and BCR methods yields an NPV of -Rp46,559,051,059, indicating an economic loss for the project. However, the positive BCR value of 2.32 suggests potential benefits in preventing losses from poor sanitation. Therefore, the IPAL project is considered feasible for continuation by the Bogor City Government, with special attention to operational budgeting.